Pembelajaran dengan Metode Accelerated Learning pada Materi Keliling dan Luas Lingkaran - Suci Yuniati (Beta: Jurnal Tadris Matematika, 2012)
This paper presents the result of a study on learning theory with the method of accelerated learning on the circumference and area of ​​a circle of material. This method is one method of learning that gives students the opportunity to develop themselves. The role of teacher as the giver of knowledge turns into a facilitator who facilitates students to learn and build their own knowledge. Students themselves should build the new knowledge from prior knowledge which is not memorizing. In addition, accelerated learning method makes students to be more active and the learning result becomes more meaningful as well as the teacher becomes more creative by creating a fun learning environment. Method of accelerated learning is divided into six basic steps. The six basic steps can be remembered easily by using the abbreviation of MASTER as follows: 1) Motivating Your Mind, 2) Acquiring The Information, 3) Searching Out The Meaning, 4) Triggering The Memory, 5) Exhibiting What You Know, dan 6) Reflecting How You,ve Learned. With the accelerated learning method, teachers are expected to implement and use it as an alternative learning method in the classroom.